Low X-ray luminosity galaxy clusters – II. Optical properties and morphological content at 0.18 < z < 0.70 - Nilo Castellon, Jose Luis Emilio (2013)
This is the second of a series of papers on low X-ray luminosity galaxy clusters, in which we present the r′, g′ and i′ photometry obtained with Gemini Multi-Object Spectrograph IMAGE at Gemini North and South telescopes for seven systems in the redshift range of 0.18 to 0.70. Optical magnitudes, colours and morphological parameters, namely, concentration index, ellipticity and visual morphological classification, are also given. At lower redshifts, the presence of a well-defined red cluster sequence extending by more than 4 mag showed that these intermediate-mass clusters had reached a relaxed stage. This was confirmed by the small fraction of blue galaxy members observed in the central regions of ∼0.75 Mpc. In contrast, galaxy clusters at higher redshifts had a less important red cluster sequence. We also found that the galaxy radial density profiles in these clusters were well fitted by a single power law. At 0.18 < z < 0.70, we observed an increasing fraction of blue galaxies and a decreasing fraction of lenticulars, with the early-type fraction remaining almost constant. Overall, the results of these intermediate-mass clusters are in agreement with those for high-mass clusters.